SISTEM INFORMASI PENGENDALIAN STOK BARANG PADA TOKO PUTRA GUSUNG MENGGUNAKAN METODE MRP - Natalia Sugito; Abdullah; Sudirman (STMIK KHARISMA Makassar, 2018)
This research aims to design Information System of Stock Control by Using Material Requirement Planning (MRP) Method that can assist Putra Gusung in controlling the stock of goods. This research is divided into five stages, that is: Problem Identification, System Requirements Analysis, System Design, Implementation, and System Testing. System design include the data modeling using Entity Relationship Diagram (ERD) and system modeling using Data Flow Diagram (DFD), then implemented using the Microsoft Visual Studio 2010 programming language and MySQL as the database. Furthermore, the system was tested using black-box testing method.